Przywództwo polityczne a przepisy Konstytucji RP z 1997 roku (Politeja, 2022)
POLITICAL LEADERSHIP AND THE RULES OF THE CONSTITUTION OF REPUBLIC OF POLAND FROM 1997The main aim of this article is the analysis of how “political leadership” – a theoretical category from the political science – could be used in the legal analysis of the rules of the Polish Constitution from 1997. There are three research paths analysing the rules of the Constitution inspired by the studies concerning political leadership. The first one attempts to answer the question: which public office possessing competences regulated in the Constitution allows its holder to be a political leader. The next path faces the problem if constitutional rules require special qualifications for holders of the most important public offices in Poland. The last path is the analysis whether the rules of the Constitution are against the political leadership regarded as the ability of one person (political leader) to undertake autonomous decisions crucial for the state and citizens. The conclusions of this analysis are as follows: (1) holding the office of President of the Council of Ministers is best suited for performing the role of political leader, (2) the rules of the Constitution do not require special qualifications for holding the office of the President of Republic or Prime Minister and (3) they are against the conception of political leadership as understood above.